If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (x + -2) + (x + -8) = 50 Reorder the terms: X + (-2 + x) + (x + -8) = 50 Remove parenthesis around (-2 + x) X + -2 + x + (x + -8) = 50 Reorder the terms: X + -2 + x + (-8 + x) = 50 Remove parenthesis around (-8 + x) X + -2 + x + -8 + x = 50 Reorder the terms: -2 + -8 + X + x + x = 50 Combine like terms: -2 + -8 = -10 -10 + X + x + x = 50 Combine like terms: x + x = 2x -10 + X + 2x = 50 Solving -10 + X + 2x = 50 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '10' to each side of the equation. -10 + X + 10 + 2x = 50 + 10 Reorder the terms: -10 + 10 + X + 2x = 50 + 10 Combine like terms: -10 + 10 = 0 0 + X + 2x = 50 + 10 X + 2x = 50 + 10 Combine like terms: 50 + 10 = 60 X + 2x = 60 Add '-2x' to each side of the equation. X + 2x + -2x = 60 + -2x Combine like terms: 2x + -2x = 0 X + 0 = 60 + -2x X = 60 + -2x Simplifying X = 60 + -2x
| 10=7-3(4m-1) | | 10x-5y=11 | | 77=2x+9x | | 5350=-10x^2+325x+3100 | | -3/-3= | | x(x*0.06)=1500 | | 7x-8x=11 | | y+p+q=r | | 6/14=5/n | | 36-(12)= | | -6r-7=-19 | | X^2+x-12=18 | | V/12=10/2 | | 36-(-12)=48 | | (2z+1)(2z-5)= | | 8/15-2/5= | | 2a+4=5 | | 1-2k-3k=-4 | | r+p+q=y | | (y-3)(y+4)= | | 6(p+8)+3(-2p-1)=48 | | y+r+q=p | | 10/12=2/n | | p+r+y=q | | P/8=13/2 | | p+y+r=q | | 15h+5=e | | r+q+y=p | | 4(7/4-b)=3-b | | -5x-7x+5=29 | | 4x-3+8=92 | | r+q+p=y |